Maximizing Returns: Bagaimana Investor Dapat Memanfaatkan Informasi Tentang Kebijakan Dividen Dan Profitabilitas Perusahaan ? Bagaimana Investor Dapat Memanfaatkan Informasi Tentang Kebijakan Dividen Dan Profitabilitas Perusahaan - Wargadalam, Winanda Wahana (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2024)
This study focuses on investors' decisions in managing their investments, particularly in the financial sector. The study emphasizes the importance of a company's financial performance and the need for companies to be proactive in achieving business goals. The study also emphasizes the importance of a strong relationship between a company's financial performance and profitability. The agency theory refers to the relationship between agents and principals, in which agents make decisions based on the company's resources. This can lead to conflicts of interest, such as agency problems. Dividend payout ratio (DPR) is a measure of the company's return on assets (ROA) and return on equity (ROE). This study uses a quantitative research method to analyze and interpret data from various financial indicators, including dividend payout ratio, return on asset, return on equity, total asset turnover, and Tobin's Q. The study also uses the linear regression method to analyze the simultaneous and parsial effects of the company's financial performance. The results provide valuable insights into the company's performance and potential areas for improvement. In conclusion, the study provides valuable insights into the performance of companies in the ASEAN region.